Hyaluronic acid-based hydrogels: As an exosome delivery system in bone regeneration - Deng, Huiling; Wang, Jiecong; An, Ran (Frontiers in Pharmacology, 2023)
Exosomes are extracellular vesicles (EVs) containing various ingredients such as DNA, RNA, lipids and proteins, which play a significant role in intercellular communication. Numerous studies have demonstrated the important role of exosomes in bone regeneration through promoting the expression of osteogenic-related genes and proteins in mesenchymal stem cells. However, the low targeting ability and short circulating half-life of exosomes limited their clinical application. In order to solve those problems, different delivery systems and biological scaffolds have been developed. Hydrogel is a kind of absorbable biological scaffold composed of three-dimensional hydrophilic polymers. It not only has excellent biocompatibility and superior mechanical strength but can also provide a suitable nutrient environment for the growth of the endogenous cells. Thus, the combination between exosomes and hydrogels can improve the stability and maintain the biological activity of exosomes while achieving the sustained release of exosomes in the bone defect sites. As an important component of the extracellular matrix (ECM), hyaluronic acid (HA) plays a critical role in various physiological and pathological processes such as cell differentiation, proliferation, migration, inflammation, angiogenesis, tissue regeneration, wound healing and cancer. In recent years, hyaluronic acid-based hydrogels have been used as an exosome delivery system for bone regeneration and have displayed positive effects. This review mainly summarized the potential mechanism of HA and exosomes in promoting bone regeneration and the application prospects and challenges of hyaluronic acid-based hydrogels as exosome delivery devices in bone regeneration.